Pattern and consequences of first visits to obstetricians/gynecologists by adolescents: a nationwide study in Taiwan - Yeh, Hsiao-Yun; Chen, Yu-Chun; Su, Irene; Chou, Li-Fang; Chao, Hsiang-Tai; Chen, Tzeng-Ji; Hwang, Shinn-Jang (Journal of the Chinese Medical Association, 2010)
Background: - Some adolescents have special health care needs. Privacy concerns, unawareness or ethnical/cultural factors are barriers to women visiting obstetricians/gynecologists (OB/GYNs). The utilization of OB/GYN services by adolescent girls is seldom reported. The aim of this study was to investigate the pattern and consequences of first visits to OB/GYNs by adolescent girls within the National Health Insurance in Taiwan. - Methods: - From the 1-million cohort dataset of the National Health Insurance Research Database spanning from 1996 to 2007, adolescent girls visiting OB/GYNs for the first time were identified. The characteristics of first visits were analyzed. Their follow-up visits and admissions within 1 year after their first visits to OB/GYNs were traced. - Results: - In 2006, only 5.8% (n = 2,682) of 46,582 adolescent girls in our study cohort had their first visits to OB/GYNs: 46.7% with diagnoses of menstrual disorders and 14.8% with diagnoses related to inflammatory or infectious diseases of the genital organs. The examination most frequently ordered was pregnancy test (for 19.9% of these first visits). Very few (0.4%) first visits were for preventive services. Among the infrequent admissions (85 admissions of 75 girls) to obstetric/gynecology wards within 1 year after first visits, the majority (74 of 85 admissions) were pregnancy-related. - Conclusion: - The leading motivating factor for first visits to OB/GYNs by adolescent girls was menstrual disorders. The majority of subsequent admissions were pregnancy-related, indicating that adolescent pregnancy deserves further attention.